Formaldehyde trapping by radical initiated reaction on hydrogenated boron nitride - Cuba-Supanta, G (2019)
We thank DGAPA, UNAM project IN101019, and CONACYT grant A1-S-9070 of the Call of Proposals for Basic Scientific Research 2017–2018 for partial financial support. G.C.S. thanks Cienciactiva for financial support through the Doctoral Scholarship Program in Peruvian Universities (contract number 218-2014-FONDECYT). J.G.S thanks Aldo Rodriguez Guerrero for technical support. Calculations were performed in the DGCTIC-UNAM Supercomputing Center, project LANCAD-UNAM-DGTIC-051.